Veiled Desires: Intimate Portrayals of Nuns in Postwar Anglo-American Film - Aughtry, Matthew (The journal of religion and film, 2017)
This is a book review of Sabine, Maureen. Veiled Desires: Intimate Portrayals of Nuns in Postwar Anglo-American Film. New York : Fordham UP, 2013.